SIKAP TOLERANSI ANTAR UMAT BERAGAMA DALAM MENJALANKAN NILAI-NILAI MODERASI BERAGAMA DIMASYARAKAT PERUMAHAN PERMAI ASRI 1 SRAGEN - Istiqomah, Wulandari (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
Indonesia is rich in diversity, one aspect of its diversity is its various religions. Some of the religions officially recognized by the government are Islam, Christianity, Catholicism, Hinduism, Buddhism and Confucianism. It is also unusual that in Sragen there is also a traditional or local religion called the Jawen religion. This discussion of religious moderation aims to see the attitude of tolerance that is maintained between religious communities in one of the city housing complexes in Central Java, namely Sragen. How is this attitude of harmony and tolerance mutually maintained from the beginning of being neighbors (2013) until now. This research is a type of qualitative research in the form of field research which involves direct observation and interaction of research subjects in the environment and library research sourced from journals and book reading. In this case, it is known that an attitude of mutual respect for one another and an attitude of harmony must always be carried out by every resident in the Permai Asri 1 Sragen housing complex, because this is one of the rules here and the people also uphold a sense of brotherhood as evidenced by the regular meetings held once a month. This meeting discusses the vision and mission for the future (whether changes need to be made or not), resolves any conflicts that arise, and discusses major events such as the 17 August Celebration, the anniversary of Sragen City and Halal bihalal, which needs to be emphasized that this association is not for exchanging argumentation of beliefs with family members who have different beliefs. The community here upholds an attitude of tolerance, which means tolerance is respecting differences in social relationships (communication) that are applied in social life, so that there are shared boundaries of what can and cannot be done. This is the main point of the explanation regarding religious moderation in the Permai Asri 1 Sragen housing complex. It is hoped that each family can always provide an environment and space for tolerance, so that they can always respect and appreciate each other's beliefs and there is no sense of wariness regarding rights, obligations and beliefs